Integrating Market-Oriented Social Responsibility into the Mining Sector: Enhancing Stakeholder Trust, Brand Equity, and Sustainable Development - Iranmanesh, Saeid; Khanlari , Amir (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to explore the integration of market-oriented social responsibility (MOSR) within the mining sector and its impact on stakeholder trust, brand equity, and sustainable development.Methodology: A mixed-methods approach was employed, utilizing data from mining stakeholders analyzed through structural equation modeling to examine how MOSR dimensions (economic, social, and environmental) contribute to stakeholder trust, loyalty, and corporate reputation.Findings: MOSR significantly influences brand equity and stakeholder advocacy, with stakeholder trust acting as a critical mediating factor. Transparent communication and stakeholder engagement amplify the effects of MOSR initiatives.Conclusion: Integrating MOSR into mining operations can enhance brand equity and stakeholder trust, fostering sustainable development. The study highlights the need for community-focused projects and innovative sustainability reporting. Practical recommendations include designing integrated MOSR strategies to align corporate objectives with societal and market needs.